The runaway jury - Grisham, John. (New York : Doubleday, 1996)
They are at eh center of a multimillion-dollar legal hurricane: twelve men and women who have been investigated, watched, manipulated, and harassed by high-priced lawyers and consultants who will stop at nothing to secure a verdict. Now the jury must make a decision in the most explosive civil trial of the century, a precedent-setting lawsuit against a giant tobacco company. But only a handful of people know the truth: that this jury has a leader, and the verdict belongs to him...
Keywords: Legal stories